Effects of elevated CO2 on the phytoremediation efficiency of Noccaea caerulescens. (December 2019) - Luo, Jie; Yang, Ge; Igalavithana, Avanthi Deshani; He, Wenxiang; Gao, Bin; Tsang, Daniel C.W.; Ok, Yong Sik
Abstract: Concentrations of atmospheric carbon dioxide have been continuously increasing, and more investigations are needed in regard to the responses of various plants to the corresponding climatic conditions. In particular, potential variations in phytoremediation efficiency induced by global warming have rarely been investigated. Objective of this research was to evaluate the changes in phytoremediation efficiency of Noccaea caerulescens exposed to different concentrations of CO2 . The concentrations of CO2 in the elevated CO2 treatments were adjusted to 550 ± 50 ppm to match the level of atmospheric CO2 predicted in 2050–2070. Compared to ambient controls (400 ppm), biomass yields and metal concentrations of N. caerulescens increased under elevated CO2 conditions, thus indicating that the phytoremediation efficiency of the species could increase in higher CO2 environment. In addition, water soluble and exchangeable Pb and Cu concentrations in soils decreased under elevated CO2 conditions, which reduced the leaching risks of the metals. The concentrations of malondialdehyde (MDA) of N. caerulescens decreased to different degrees with the increased CO2 concentrations. The overall findings suggested that elevations in CO2 can reduce the oxidative damage caused by metals in this species. The phytoremediation efficiency of N. caerulescens grown in multiple metal-enriched soils could be enhanced with global warming. Graphical abstract: Image 1 Highlights: Elevated CO2 increased the biomass yield of Noccaea caerulescens . Chlorophyll contents in N. caerulescens increased with the elevated CO2 . Elevated CO2 decreased oxidative damage caused by excessive metals. Elevated CO2 decreased the leaching risks of non-hyperaccumulated metals. Abstract : Elevated atmospheric CO2 increased the phytoremediation efficiency of Noccaea caerulescens .